Trading Zones and the Stickiness of Ideas - Sarah Williams Goldhagen (Footprint)
Following up on her description of architecture as a discourse, or a long and complex conversation sustained by a multitude of professionals, Sarah Williams Goldhagen elaborates on the way this discourse has evolved over the decades, shifting from style as conveyor of meaning, to climate and technique as central concerns of the contemporary architect. Ranging from current historiography and its role in pedagogy, to the different agendas that inform architecture practice and the architecture competition in our time, this conversation provides a series of powerful leads for further investigation.